Improvement of luminescence properties of rubidium vanadate, RbVO3, phosphors by erbium doping in the crystal lattice. (31st May 2017) - Kim, S. W.; Hasegawa, T.; Muto, M.; Toda, A.; Kaneko, T.; Sugimoto, K.; Uematsu, K.; Ishigaki, T.; Toda, K.; Sato, M.; Koide, J.; Toda, M.; et al.
Abstract : The thermal quenching effect of RbVO3 phosphor was effectively improved by Er 3+ doping into the lattice, as a result, the emission intensity of the phosphor was successfully enhanced. Abstract : Greenish-white emitting Rb1− x Er x VO3 (0 ≤ x ≤ 0.10) phosphors were synthesized by a conventional solid state reaction method. The thermal quenching effect of the RbVO3 phosphors was effectively improved by Er 3+ doping into the RbVO3 lattice. Consequently, the emission peak intensity of the phosphors was successfully enhanced by Er 3+ doping, and the internal quantum efficiency of Rb0.99 Er0.01 VO3 under excitation at 360 nm was 80%.